Beyond Japan : The Dynamics of East Asian Regionalism - Shiraishi, Takashi, 1950-; Katzenstein, Peter J. (Book collections on Project MUSE., 2006)
Have Japan's relative economic decline and China's rapid ascent altered the dynamics of Asian regionalism? Peter Katzenstein and Takashi Shiraishi, the editors of Network Power, one of the most comprehensive volumes on East Asian regionalism in the 1990s, present here an impressive new collection that brings the reader up to date. This book argues that East Asia's regional dynamics are no longer the result of a simple extension of any one national model. While Japanese institutional structures and political practices remain critically important, the new East Asia now under construction is more than, and different from, the sum of its various national parts. At the outset of a new century, the interplay of Japanese factors with Chinese, American, and other national influences is producing a distinctively new East Asian region. Contributors: Dieter Ernst, East-West Center, Honolulu; H. Richard Friman, Marquette University; Derek Hall, Trent University; Natasha Hamilton-Hart, National University of Singapore; Peter J. Katzenstein, Cornell University; William W. Kelly, Yale University; David Leheny, University of Wisconsin-Madison; Naoko Munakata, Japanese Ministry of Economy, Trade, and Industry; Nobuo Okawara, Kyushu University; T.J. Pempel, University of California, Berkeley; Takashi Shiraishi, National Graduate Institute for Policy Studies, Tokyo; Merry I. White, Boston University.